Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage dan Pertumbuhan Penjualan terhadap Penghindaran Pajak pada Perusahaan Sektor Property and Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2017 - 2020 - Salma, Afia; Kurniawan, Budi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The study of this research is to determine the impact of corporate size, leverage, profitability, and sales growth on tax avoidance among listed property and real estate companies in Indonesia from 2017 – 2020. The research uses secondary data from exchange listed financial statements. This study uses secondary data on the financial statement on listed of property and real estate from. The sample were drawn using a targeted sampling technique. The population was 98 companies, the sample was 21 companies, and there were 84 observation. Data anaylisis used panel data regression with the Stata 16 program. The result show that company size and sales growth have a positive and insignificant impact on the tax avoidance. ROA and DER have a negative impact on the tax avoidance.